Abstracts of current studies : the World Bank research program - World Bank; World Bank. (Washington, D.C. : World Bank, 1979)
Bank research projects investigate a broad range of issues in wide variety of settings. This volume reports on research projects initiated, under way or completed in fiscal 1999 (July 1, 1998, through June 30, 1999), The abstracts in the volume describe, for each project, the questions addressed, the analytical methods used, the findings to date, and their policy implications. Each abstract also identifies the expected completion date, the research team, and any reports or publications produced. The abstracts cover 202 research projects grouped under nine headings:a) poverty and social welfare; b) education and labor markets; c) environmentally sustainable development; d) macroeconomics; e) international economics; f) domestic finance and capital markets; g) transition economies; and h) private sector development and public sector management.
aia 23/8/16
Ref.
Keywords: World Bank --- Research; Economic assistance; Technical assistance; Economic development; Economic assistance; Technical assistance